The importance of a physical activity program for patients with multiple sclerosis on life satisfaction and psychological well-being - Pedro, Luísa (2013)
Multiple sclerosis (MS) is a chronic disease of the central nervous system that affects more frequently young women. MS is a progressive disease and unpredictable, resulting in some cases, disability, and limitations in physical, psychological, and social. In this study, we investigate the effect of an intervention program to promote physical activity in individuals with MS on psychological well-being (BEP) and life satisfaction (SV). Methods – This is a quasi-experimental study. We use the scale of life satisfaction (7 items) and psychological well-being component inventory mental health (14 items). The study includes 24 patients with a mean age of 44, 58.3% are women, 37.5% are married, 67% are retired, with an education of 12.5 years, diagnosed at least 1 year. The program consists of an intervention to promote physical activity in a group of eight people, weekly, for 90 minutes, for seven weeks. To analyze the results we used SPSS version 20. Results – We used the Wilcoxon test for variables BEP and SV, obtained from the assessment before the intervention program and end of the program. We found that listening to significant changes between the two times p <0.01 in both variables, with higher results at the end of the intervention program. Discussion/Conclusions – Through reading the results we can see that the implementation of a program to promote physical activity in patients with MS, using a model in a holistic and integrated biopsychosocial perceptive improve SV and BEP in these patients.